Analisa Perawatan Mesin Dengan Metode Reability Centered Maintenance (RCM) Terhadap Mesin Over Wrapping E3060 Line 1 - Pratama, Yudha; Haspak Pradipto, Gigih; Ngudi Wiyatno, Tri (DPPM Universitas Pelita Bangsa, 2024)
Companies in the pharmaceutical industry produce health products such as herbs and medicines. Due to intense competition, companies must optimize the use of their machines to increase productivity. In machine maintenance PT. Kalbe Farma, the total production treatment method is used, but its application is not maximized, as happened with the machines in line 1. PT. Kalbe Farma produces Promag products, which are in great demand in the market, with the production of 30 to 40 batches a month. In February 2023, the percentage breakdown on the E3060 Overwrapping machine was very high, reaching 11.59%. However, the breakdown should not exceed 10% of the Working Time. Therefore, damage can cause many losses such as reduced quantities of products, increased costs and other losses. A machine maintenance Program is required to ensure machine optimization. Using a reliability-centered (RCM) maintenance approach, this study investigated the maintenance of the e3060 wrapper and found critical components. The results showed that the Sade Lipat component has the highest damage frequency of 15 times and has the highest RPN value of 128 which indicates that this component is the component that experiences the most downtime. This RCM methodology helps identify maintenance actions and recommendations for implementing better Predictive Maintenance, Preventive Maintenance, and Inventory Management so that equipment remains optimal according to its function Keywords: Pharmaceutical Industry, Reability Centered Maintenance (RCM), Total Productive Maintenance (TPM)